Preparation and Characterization of Activated Carbon from the Sea Mango (Cerbera Odollam) with Impregnation in Phosphoric Acid (H3PO4) - A. Nur Hidayah; M. A. Umi Fazara; Z. Nor Fauziah; M. K. Aroua (ASEAN Journal of Chemical Engineering, 2015)
The properties of the activated carbon from Sea Mango (Cerbera Odollam) prepared from chemical and physical activation was studied. The sample was impregnated with phosphoric acid (H3PO4) at the impregnation ratio of precursor to activant as 1:2 and followed by thermal activation at 500 °C with different flowing gas i.e. nitrogen (N2), carbon dioxide (CO2), steam and at the absent of any gases for duration of 2 hours. The sample experienced two different steps of preparation which were Method 1 and Method 2. In Method 1, the precursor will be thermally heated after the chemical activation process, and the samples were denoted as RIHM1-N, RIHM1-CO2, RIHM1-S and RIHM1-A which utilize either N2, CO2, steam and absent of any gases, respectively. Meanwhile in Method 2, the carbonization process with N2 flow at 200 °C was done prior to chemical and thermal activation. This type of treatment method was denoted as RCIHM2-N, RCIHM2-CO2 RCIHM2-S and RCIHM2-A, which use the same flowing gases as described previously. The surface area of the activated carbon was determined using standard method (ASTM) of iodine test. A higher iodine number reading was given by the sample prepared via Method 2 i.e. 1021.74 mg/g, 1069.98 mg/g 902.40 mg/g and 1040.58 mg/g for sample RCIHM2-N, RCIHM2-CO2, RCIHM2-S and RCIHM2-A, respectively. For sample prepared via Method 1, the iodine number measurement for sample RIHM1-N, RIHM1-CO2, RIHM1-S and RIHM1-A were 896.480 mg/g, 810.900 mg/g, 973.70 mg/g and 856.217mg/g, respectively.